Differential aspects of ascending thoracic aortic dissection and its treatment: the North American experience - Preventza, Ourania; Coselli, Joseph S. (Annals of Cardiothoracic Surgery; Vol 5, No 4 (July 01, 2016): Type A Aortic Dissection (II), 2016)
Acute type A aortic dissection is a deadly disease with significant morbidity and mortality. We describe the differential aspects of the disease and the North American experience with its treatment.